2013
DOI: 10.1007/s11356-013-2355-9
|View full text |Cite
|
Sign up to set email alerts
|

Compaction stimulates denitrification in an urban park soil using 15N tracing technique

Abstract: Soils in urban areas are subjected to compaction with accelerating urbanization. The effects of anthropogenic compaction on urban soil denitrification are largely unknown. We conducted a study on an urban park soil to investigate how compaction impacts denitrification. By using 15 N labeling method and acetylene inhibition technique, we performed three coherent incubation experiments to quantify denitrification in compacted soil under both aerobic and anaerobic conditions. Uncompacted soil was set as the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Urine application can increase pH due to hydrolysis of organic matter, increasing both carbon and N turnover (Monaghan and Barraclough, 1993;Selbie et al, 2015). Other differences between soils, such as P availability (Mehnaz and Dijkstra, 2016) and soil structure (Li et al, 2014) have been suggested previously as significantly influencing N dynamics, particularly for in situ studies.…”
mentioning
confidence: 99%
“…Urine application can increase pH due to hydrolysis of organic matter, increasing both carbon and N turnover (Monaghan and Barraclough, 1993;Selbie et al, 2015). Other differences between soils, such as P availability (Mehnaz and Dijkstra, 2016) and soil structure (Li et al, 2014) have been suggested previously as significantly influencing N dynamics, particularly for in situ studies.…”
mentioning
confidence: 99%
“…We found a high N removal efficiency in the mown site m1 (Table 1), which might be explained either by N removal with hay or due to soil compaction by the mowing machinery, which may stimulate denitrification by lowering the oxygen content in soil pores (Li et al, 2014). However, this does not have to be a result of mowing, as N removal in the unmown sites was also substantial.…”
Section: The Impact Of Mowing On N Removalmentioning
confidence: 83%
“…Another potential interaction is caused by soil compaction due to the pressure exerted by mowing machinery. Soil compaction has been reported to stimulate denitrification by increasing water-filled pore space in the soil, thereby lowering the oxygen supply (Li et al, 2014. However, such changes might promote internal release of P due to favoured reduction of redox-sensitive iron(III)-P binding forms (Zak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2006; Li et al . 2014). In combination with the fact that at the national scale Cu was found to be the most significant and widespread pollutant metal in Chinese urban soils (Wei & Yang 2010; Luo et al .…”
Section: Discussionmentioning
confidence: 99%